Canadian Strategy Against Gender-Based Violence and Gaps - Lanyan Chen; Jennifer McCarthy; Miao Chen (Societies)
Promoting the Essential Services Package (ESP) for Women and Girls Subject to Violence has led to an emphasis on legislative commitments to a survivor-centred strategy. Such legislation includes provisions for fiscal planning, standards of services, and official programs to support networks of community-based interventions to build capacity, share information, and co-generate knowledge across regions. This study identifies gaps in the Canadian strategy against gender-based violence in the operation of mechanisms for coordinating multi-sectoral trauma-informed “wrap-around” services that prioritize survivors in their distinct and diverse contexts and communities. It also recommends ways to transform the Canadian strategy in a global context.